Application of Smart Tourism to Nature-Based Destinations - Silva, Francisco (2020)
This chapter aims to address two main themes and their possible articulation. The first explores the management of products and destinations strictly associated with nature-based tourism. The second is associated with creative and smart tourism. The connection of these two themes represents an innovative approach considering that both smart and creative tourism are closely linked to smart cities concept and urban spaces, while there is still no widespread application to other territories. The application of creative and smart tourism principles to new realities as nature-based tourism is assumed as a new challenge that requires well supported evidence and the development of sustained approaches.